In‐gap states of In2O3 single crystals investigated by scanning tunneling spectroscopy. Issue 1 (28th October 2013) - Braun, Dorothee; Scherer, Valentina; Janowitz, Christoph; Galazka, Zbigniew; Fornari, Roberto; Manzke, Recardo
Abstract The influence of intrinsic point defects on the electronic structure of n‐type In2O3 single crystals grown by two methods, namely chemical vapor transport and from the melt, was examined by scanning tunneling spectroscopy. This method is a very surface sensitive technique for measuring the local density of states. So far not resolved states within the fundamental band gap have been observed. The gap states have been studied at different crystals and after several annealing treatments in an oxidizing atmosphere. The spectroscopic results will be compared to state of the art DFT‐calculations revealing hints on the origin of the gap states of In2O3 to be due to oxygen vacancies as well as indium and oxygen interstitials.